2012
DOI: 10.1017/s0024282912000138
|View full text |Cite
|
Sign up to set email alerts
|

Fungal-algal interactions inRamalina menziesiiand its associated epiphytic lichen community

Abstract: Lichens are a fascinating example of a symbiotic mutualism. It is still uncertain which processes guide fungal-photobiont interactions, and whether they are random or of a more complex nature. Here, the fungal-algal interactions in Ramalina menziesii and co-occurring taxa are analyzed by using DNA sequences of the algal Internal Transcribed Spacer region (ITS), to investigate fungalalgal associations in juvenile R. menziesii and allied species. Algal species were identified by a combination of BLAST searches, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…The lichen disperses mainly sexually on a local scale ( Werth and Sork, 2008 ). The photobiont has been previously determined as Trebouxia decolorans Ahmadjan based on samples from southern California Sork, 2008 , 2010 ;Werth, 2012 ). Trebouxia decolorans is a common photobiont in lichens and has previously been found in species such as Xanthoria parietina from Europe ( Beck and Mayr, 2012 ;Nyati et al, 2013 ;Nyati et al, 2014 ) and in X. hasseana from western North America ( Werth, 2012 ).…”
Section: Study Species -mentioning
confidence: 98%
“…The lichen disperses mainly sexually on a local scale ( Werth and Sork, 2008 ). The photobiont has been previously determined as Trebouxia decolorans Ahmadjan based on samples from southern California Sork, 2008 , 2010 ;Werth, 2012 ). Trebouxia decolorans is a common photobiont in lichens and has previously been found in species such as Xanthoria parietina from Europe ( Beck and Mayr, 2012 ;Nyati et al, 2013 ;Nyati et al, 2014 ) and in X. hasseana from western North America ( Werth, 2012 ).…”
Section: Study Species -mentioning
confidence: 98%
“…Free-living photobionts must be able to survive without the positive effect of ecological buffering provided by the mycobiont. There is a growing body of evidence that lichen photobionts are specialized to particular habitats and ecological conditions (Piercey-Normore 2006;Yahr et al 2006;Werth & Sork 2010;Casano et al 2011;Fernandez-Mendoza et al 2011;del Hoyo et al 2011;Peksa & Skaloud 2011;Werth 2012;del Campo et al 2013;Domaschke et al 2013). Our study is in concordance with those studies and showed a distinct ecological, that is altitudinal, niche differentiation in the photobiont Dictyochloropsis eticulata (Table 4, Fig.…”
Section: Ecological Specialization Of the Lobaria Pulmonaria Symbiosismentioning
confidence: 99%
“…decolorans that is much more broadly distributed than the lichen‐forming fungus R. menziesii , and this suggests that this algal species has very different environmental tolerances. T. decolorans has been reported from several continents and in association with diverse fungal species (Helms et al ., ; Beck & Mayr, ; Werth, ; Muggia et al ., ; Nyati et al ., ,b). The wider distributional range and low specificity of T .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the green alga T. decolorans that is much more broadly distributed than the lichen-forming fungus R. menziesii, and this suggests that this algal species has very different environmental tolerances. T. decolorans has been reported from several continents and in association with diverse fungal species (Helms et al, 2001;Beck & Mayr, 2012;Werth, 2012;Muggia et al, 2013;Nyati et al, 2013a, b). The wider distributional range and low specificity of T. decolorans imply that this photobiont may have persisted under more diverse environmental conditions and experienced a population history distinct from the mycobiont R. menziesii.…”
Section: No Co-migration Between Mycobionts and Photobiontsmentioning
confidence: 99%